Pengaruh Kepercayaan, Kemudahan, dan Manfaat Digital Payment Sebagai Alat Pembayaran Terhadap Perilaku Konsumtif Individu Dengan Digital Savvy Sebagai Variabel Moderating - Rindi Safira; Sugianto Sugianto; Rahmat Daim Harahap (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
The research aims to determine the effect of trust, convenience, and benefits of digital payments as a means of payment on individual consumptive behavior with digital savvy as a moderating variable. This study uses a quantitative method in data analysis where the data comes from the results of questionnaires that have been distributed to the respondents. The population in this study is Medan city residents, especially those aged 18 -25 years (Gen Z) with a sample of 100 respondents. To determine the sample using a purposive sampling technique, namely by determining the criteria for respondents including residents aged 18-25 years (Gen Z), domiciled in the city of Medan and using digital payments. The collected data were analyzed using SPSS 25 with Multiple Linear Regression and Moderate Regression Analysis (MRA). In accordance with the tests that have been carried out, the results show that trust, convenience and benefits of digital payments have an effect on consumptive behavior. From the data test, it was found that the R square value was 0.552. It can be concluded that the variables of trust, convenience and benefits of digital payments contribute 55.2% to consumptive behavior while the remaining 44.8% are influenced by other variables. The MRA test that has been carried out also proves that Digital Savvy as a Moderating Variable is able to influence and strengthen the relationship between variables with increased R square results after being moderated. Keywords: Digital Payment; Consumptive behavior; Digital savvy; Perspective of Islamic Economics.